Atrial and ventricular function in thalassemic patients with supraventricular arrhythmias - Vitantonio Di Bello; Salvatore Licciardi; Enrica Talini; Elisa Nicolosi; Ines Monte; Davide Capodanno (Heart International, 2009)
The aims of this study were to evaluate through Color Doppler Myocardial Imaging (CDMI) echocardiography if atrial or ventricular myocardial alterations could be detectable in patients with thalassemia major (THAL) and if these alterations could be considered as predictive elements for supra-ventricular arrhythmic events. Twenty-three patients with THAL underwent clinical and electrocardiographic evaluation; patients were grouped in THAL1 (9 with supra-ventricular arrhythmias) and THAL2 (14 without arrhythmias); 12 healthy subjects were considered as control group (C). We examined through conventional 2D Color Doppler echocardiography some morphological and functional parameters regarding left ventricular (LV) systolic and diastolic function, and through CDMI the velocities at mitral annulus level, the regional LV and left atrial (LA) strain and strain rate. All THAL patients had LV dimension (pless than 0.05), LA area (p less than 0.01) and E/Em ratio (pless than 0.001) to be significantly higher than controls. The mitral annulus longitudinal velocities were significantly lower in THAL1 than in THAL2 (pless than 0.001); the E/Em ratio was higher in THAL1 than THAL2 (pless than 0.001). The THAL1 showed a lower systolic strain rate of atrial wall than THAL2 and C (pless than 0.05). The multiple regression highlighted a significantly inverse correlation among E/Em and atrial strain (pless than 0.02). CDMI showed both THAL subgroups had subtle systolic and diastolic left ventricular myocardial alterations, which could represent the onset of developing “iron cardiomyopathy” and are related to supra-ventricular arrhythmia. Monitoring these parameters in the THAL patients could contribute to decisions about follow-up and therapy.